O letramento literário na formação docente de futuros professores de literatura - Luciana Mara Torres Buccini (2024)
This research, based on the investigations about literary literacy in the school environment and in the field of initial teacher education, proposes a reflection on the academic and professional formation of individuals who might work as Portuguese and Literature teachers in Basic Education, more restrictively focusing on their literary backgrounds and proposals of literature teaching practices. The general objective of this investigation is to better understand pathways, diverse knowledge, and conceptualizations on the teaching of Literature disclosed by Languages undergraduate students. This research is grounded in discussions about literacy (STREET, 2012, 2014; SOARES, 2006), literary literacy (PAULINO, 1999a, 2010, 2014; COSSON, 2006, 2014, 2020), and in-school literature teaching (SOARES, 2011; LAJOLO, 2018; ZILBERMAN, 2007, 2009, 2017; ROSENBLATT, 2002 [1938], LEITE, 1983). This study proposes to get acquainted with the literary repertoire and literature teaching practices perspectives envisioned by the Languages undergraduate students of a federal university located in the state of Minas Gerais. For such, this research has tracked, throughout one semester, Portuguese undergraduate students with class observations of a mandatory subject linked to the teaching of Literature in the graduation course. Initially, the students were invited to answer a questionnaire to tell their literary backgrounds – curricular-based or not. Data gathered from the activities which were part of the course subject have also composed the corpus analyzed in this investigation. The results pointed to a gap in the Literature teacher training due to the inconspicuous presence of subjects related to the teaching of Literature in the Languages course program. Moreover, readings conducted by the undergraduate students have proven how the literary formation is marked by generational issues and the heterogeneity in these repertoires. Despite such traits, it has been observed that most of the undergraduates opted to refer novels from the canon to middle-schoolers. The choice for canonical books is made by tangling these pieces to other kinds of related media, such as YouTube videos, songs, and movies. With regards to the Literature teaching practices proposals, the class plannings which demand the reading of the full/original versions of the books were highlighted, alternating between individual and shared readings. The kind of methodology that promotes in-class group interactions for building the plotsmeaning is privileged. It is also observed that the teacher is presented as a mediator of the process and a facilitator for the students to reach a deeper understanding of the social aspects addressed in the literary books.